Distributed Nodes-Based Collaborative Sustaining of Precision Clock Synchronization upon Master Clock Failure in IEEE 1588 System - Kyou Jung Son; Tae Gyu Chang (Sensors, 2020)
This paper proposes a distributed nodes-based clock synchronization method to sustain sub-microsecond precision synchronization of slave clocks upon master clock failure in IEEE 1588 PTP (precision time protocol) system. The sustaining is achieved by synchronizing the slave clocks to the estimated reference clock which is obtained from the analysis of distributed slave clocks. The proposed method consists of two clock correction functions (i.e., a self-correction and a collaborative correction, respectively). Upon master failure, the self-correction estimates a clock correction value based on the clock model which is constructed during normal PTP operation. The collaborative correction is performed in the preselected management node. The management node estimates a reference clock by collecting and analyzing clock information gathered from the other slave clocks. The performance of the proposed method is simulated by computer to show its usefulness. It is confirmed that the fifty (50) clock model-based collaborative correction maintains 10−6 second PTP accuracy for 10 min prolonged period after the master failure when tested with clock offset variations less than 50 ppm.